Efficacy and safety of intravenous thiopental for sedation during magnetic resonance imaging in pediatric patients: A retrospective analysis - Yunus O Atalay; Tomak Leman; Joseph Drew Tobias (Saudi Journal of Anaesthesia, 2017)
Introduction: Although the administration of rectal thiopental for sedation during magnetic resonance imaging (MRI) has been well described, there are limited data regarding its intravenous (IV) use in this clinical scenario. The aim of this study was to investigate the efficiency of IV thiopental for sedation during MRI in the pediatric population. Methods: A retrospective review was conducted over a 12-month period of pediatric patients who received IV thiopental for sedation during MRI. Data collected included the procedure length, the induction dose, the time to sedation, recovery time, total sedation time, and adverse events. The parents were telephoned and questioned regarding any adverse effect after discharge and their satisfaction (yes = satisfied; no = not satisfied) regarding the sedation process. Results: A total of 300 (American Society of Anesthesiology I–II status) pediatric patients received IV thiopental for sedation during MRI. The average age of the patients was 4.7 ± 3 years. Thiopental was administered as an initial IV bolus dose of 3 mg/kg, followed by additional bolus doses of thiopental (1 mg/kg) as needed to achieve a Ramsay sedation score of 4. The average procedure length was 20.7 ± 11.9 min. The average total dose of thiopental during the procedure was 5.6 ± 0.9 mg/kg. Patients recovered in an average time of 11 ± 5.6 min after a total sedation time of 31.7 ± 14.2 min. None of the patients had oxygen desaturation, adverse effects before or after discharge, and no patient required unplanned hospital admission. All parents were satisfied with the sedation process. Conclusion: IV thiopental is an effective, safe, and inexpensive medication for the sedation of children undergoing MRI.